Effect of psychological intervention of sandplay therapy on children without accompanying in Neurosurgery Department under the normalization of epidemic prevention and control (常态化疫情防控期间小儿神经外科无陪住患儿的箱庭疗法心理干预效果分析) - XIN Jie (辛杰); ZHANG Hongyang (张宏扬); ZHU Ruifang (朱瑞芳) (Association of Integrative Nursing, 2023)
Objective To explore the effect of sandplay therapy on separation anxiety and other psychological disorders of children aged 3-12 years old who were not accompanied by family members under the normalization of epidemic prevention and control. Methods Totally 170 children who were admitted to the hospital for surgery from February 2021 to May 2022 were enrolled. Random sampling methods were used to divide the children into the control group (n=85) and the intervention group (n=85) according to whether they were treated with sandplay therapy. The two groups of children were collected on the second day of hospitalization and the day of discharge Multidimensional Anxiety Scale (MASC) scores of children and adolescents and a survey of satisfaction with family members at discharge. Results . On the day of discharge from the hospital, the total scores of the MSAC scale scores and the MASC scores of each subscale of the two groups were significantly lower than those at admission(P＜0. 01). The total score of MASC in the intervention group was significantly lower than that of the control group(P＜0. 01), and the scores of injury avoidance, separation anxiety, and social anxiety were significantly lower in the intervention group than the total scores of the control group (P＜0. 01). Conclusion The responsible nurses accompany the whole process combining sandplay therapy can significantly improve the mental health of children. Sandplay therapy, as a therapeutic psychological care method, can be used as part of the comprehensive nursing plan for hospitalized children, especially those hospitalized during the epidemic. It is worthwhile further research and promotion. (目的 探讨新型冠状病毒肺炎疫情常态化防控期间运用箱庭疗法对3～12岁无家属陪住患儿的分离性焦虑等心理障碍的缓解作用。方法 纳入2021年2月-2022年5月收治入院的手术患儿170例, 采用随机抽样方法分为对照组和干预组, 各85例。对照组实施常规排班, 患儿接受常规治疗和护理; 干预组实施责任护士制, 并在对照组基础上增加箱庭疗法心理干预。收集两组患儿住院第2天及出院当天的儿童青少年多维度焦虑量表(MASC)评分。结果 出院当天两组MSAC量表评分总分及各分量表得分较入院时下降(P＜0. 01), 干预组MASC总得分低于对照组(P＜0. 01); MASC量表分量表中伤害逃避、分离性焦虑及社会焦虑得分干预组低于对照组(P＜0. 01)。结论 责任护士全程陪护联合箱庭疗法能有效改善患儿的心理健康状况, 箱庭疗法作为治疗性心理护理方法, 可以作为住院患儿, 尤其是疫情期间住院患儿的综合护理方案的一部分, 值得进一步研究及推广。)